A study of Sarcocornia A.J. Scott (Chenopodiaceae) from Western Mediterranean Europe. (3rd March 2016) - De La Fuente, V.; Rufo, L.; Rodríguez, N.; Sánchez-Mata, D.; Franco, A.; Amils, R.
Abstract : The latest publications on Sarcocornia taxonomy and phylogeny recognize six taxa in this genus on the Iberian Peninsula: S. perennis, S. fruticosa, S. alpini, S. alpini subsp. carinata, S. hispanica, and S. pruinosa . The present study represents a comprehensive revision of the different taxa in the Sarcocornia genus present in Western Mediterranean Europe by means of morphological, micromorphological and phylogenetic internal transcribed spacer (ITS) analysis. Morphological and micromorphological data were studied from Sarcocornia samples from 113 populations in coastal salt marshes and inland salt pans in Portugal, France, Spain and Italy. Sixteen new ITS sequences were obtained from Mediterranean Sarcocornia species and analysed together with previous reported data. Published karyological, ecological and biogeographical data from Western Mediterranean Europe were also reviewed. The results indicate the presence of a new species, S. lagascae, found growing in coastal Mediterranean areas of the Iberian Peninsula. The species S. fruticosa was found to be absent from the Iberian territories.